ANALISIS DAMPAK PELAKSANAAN PROGRAM CSR TERHADAP PENINGKATAN KAPASITAS USAHA MIKRO DAN KECIL (UMK) BINAAN PT XYZ - Wina, Ni Made Ayu; Arnanda, Mahardyastika Laksmita Arnanda; Ariesta Utha, Maria Ariesta Utha; Kurniawati, Kurniawati (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research investigates the impact of PT XYZ's Corporate Social Responsibility (CSR) initiatives on Micro and Small Enterprises (MSEs) in the Jabodetabek region. Focusing on MSME mentoring and revolving capital loans, the study aims to understand their effects on managerial capacity, work skills, financial capacity, and access to financing for MSEs. Utilizing a qualitative approach, in-depth interviews with PT XYZ's CSR & External Relation Division, ten mentored MSEs, and two facilitators are conducted, supplemented by secondary data from the company. Findings reveal that PT XYZ's MSE mentoring program offers practical training, mentoring, and financial aid, addressing financing challenges, enhancing product quality, and expanding market share. The revolving capital loan program also proves beneficial for various business purposes. Despite challenges like loan repayment and network expansion, these initiatives significantly contribute to local economic development, community well-being, and MSME growth in the Jabodetabek region.